Cyclic Voltammetry Analysis of Co-Electrodeposition Mechanism of rGO-Sb2Se3 Thin Films Photocathode. Issue 10 (1st January 2019) - Wang, Jun; Chen, Jianyu; Jiang, Liangxing; Liu, Fangyang; Jia, Ming; Lai, Yanqing; Li, Jie
Abstract : rGO-Sb2 Se3 thin films were deposited on ITO electrode and the complex electrochemical processes within ternary Sb-Se-GO precursor solution had been researched by cyclic voltammetry. The addition of GO can promote the deposition of Sb and Se simultaneously. In addition, the co-electrodeposition process of Sb2 Se3  which controlled by diffusion step was irreversible and was achieved by the mutual inducement of preferentially precipitated Se and subsequently deposited Sb. The influence of deposition potential was studied, for which −0.75 V∼ −0.9 V was selected as the optimal condition to obtain the ideal p-type rGO-Sb2 Se3 thin films.